HAK KEKAYAAN INTELEKTUAL DALAM INDUSTRI PARIWISATA Studi Kasus: Perlindungan Hukum Pemanfaatan Local Genius dalam Produk Pengusaha Lokal - Putri Kusuma Sanjiwani (Jurnal Ilmiah Hospitality Management, 2016)
Local entrepreneurs are still relatively weak in protecting their rights in the Intellectual Property Rights (IPR) to maintain the value and economic benefits of the work or product that they produce. These weaknesses affect many parties/foreign entrepreneurs who are trying to register their works as IPR foreign entrepreneurs. This study used empirical research by analyzing problems that occur in the field. The purpose of this study is to find out the root problems that occur in the work of local entrepreneurs that is claimed by the parties/foreign businessmen. The results showed that a local genius with anonymous ownership is claimed to be state ownership, while exploiting local genius as a result of new work, new findings and packaging into a product of private or individual ownership. Type of awareness of local entrepreneurs in obtaining intellectual property rights depends on the intended target market. The law in Indonesia is only able to protect the intellectual property rights in our country, however if it is claimed in other countries, Indonesia law could not intervene or protect it.